Financial Literacy, Investment Motivation, Risk Tolerance, and Investing Interest in Mutual Funds - Divas Nareswara, Anak Agung; Wijana Asmara Putra, I Nyoman (E-Jurnal Akuntansi; Vol 34 No 9 (2024), 2024)
Mutual funds represent investments in a variety of financial instruments, including the money market, stocks, bonds, and deposits. This study, conducted with 100 Generation Z respondents in Denpasar City, aims to empirically examine the impact of financial literacy, investment motivation, and risk tolerance on the interest in investing in mutual funds. Data was collected via questionnaires and analyzed using multiple linear regression with the SPSS software. The findings reveal that both financial literacy and investment motivation significantly enhance interest in mutual fund investments. Conversely, risk tolerance appears to have no significant effect on this interest. Theoretically, this research supports and expands knowledge related to the theory of planned behavior, motivation theory, and prospect theory. Practically, the study serves as a guide for investors in making informed decisions and enhances their understanding of mutual fund investments, investment motivations, and risk tolerance levels.